Revisiting the ASEAN Charter: Urgency and Implications - Kurnianingsih, Alfi; Kurniawan, Yandry (Universitas Medan Area, 2025)
This article examines how the ASEAN Charter, which came into force in 2008, has transformed the dynamics and effectiveness of ASEAN in addressing regional challenges, strengthening cooperation among member states, and clarifying ASEAN's identity and role in the international arena. However, the implementation of the ASEAN Charter faces implementation challenges and substantive relevance challenges. This has prompted an urgent need to review and revise the ASEAN Charter, which is no longer relevant to the rapidly changing global and regional landscape. This revision will enable ASEAN to adapt to changes, ensure its relevance, effectiveness, and readiness to meet AMS's evolving needs and priorities, and address complex and dynamic challenges in the region. The researcher conducted a desk study approach to collect primary and secondary data from 2008 – 2023. The study method is qualitative descriptive and analyzed using the triangulation method with narrative content analysis. This article concludes that the revision of the ASEAN Charter will pose risks, uncertainties, and a series of unforeseen consequences that could undermine ASEAN's stability and unity. Thus, the recommendation to ensure the relevance of the ASEAN Charter is to conduct a review focused on developing a familiar voice and resolving conflicts effectively.